Analysis and validations of operation behaviors for dual active bridge‐based unified power quality conditioner under different working conditions. (29th September 2022) - Zhao, Xiaojun; Bai, Pengshuo; Zhang, Chunjiang; Zhao, Zhide; Wang, Xiaohuan; Guo, Xiaoqiang
Abstract: In this paper, a dual active bridge‐based unified power quality conditioner (DAB‐UPQC) is constructed to solve the bulky issue caused by a line‐frequency transformer (LFT) in conventional UPQC. Since there is no LFT, the constructed DAB‐UPQC is easier to realize modular manufacturing, which further increases the flexibility of system. After adding DAB, the UPQC will present two obvious changes as follows: (a) Almost all of the grid input current flows through the series converter, resulting in an increase in the current stress of switches in the series converter. (b) The dc link is allowed to contain both low‐ and high‐voltage amplitudes due to the voltage ratio of high‐frequency transformer in DAB. Considering these two changes, the operation behaviors of DAB‐UPQC are analyzed in detail, which has the valuable significance for designs of DAB, series and parallel converters. Additionally, the characteristics and implementation conditions of soft‐switching for DAB with single‐phase‐shift (SPS) modulation are analyzed and discussed, and the battery bank is integrated on the low‐voltage side of dc link to provide continuous power to the load in the event of the grid outage or failure. Finally, the operation performances of DAB‐UPQC under the conditions of grid voltage sag/swell, nonlinear load, and grid outage are verified by using a hardware‐in‐the‐loop (HIL) experimental platform. Abstract : The DAB‐UPQC is constructed to solve the bulky issue caused by the line‐frequency transformer in conventional UPQC, so as to achieve lightweight and flexibility. Almost all the grid current flows through the SC in DAB‐UPQC, and this current may even be larger than the load current when the grid voltage fluctuates. The battery bank is connected to the low‐voltage side of dc link, which can not only reduce the number of batteries but also provide continuous electric energy output for critical loads in the event of grid outages or failures.